2013
DOI: 10.1097/inf.0b013e318280ab45
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Concordance Between the Microorganisms Detected in the Nasopharynx and Middle Ear of Children With Otitis Media

Abstract: Studies of microorganisms involved in otitis media in children often use a nasopharyngeal sample as a proxy for the middle ear fluid to test for bacteria and viruses. The question is whether such studies provide an accurate estimate of the prevalence of microorganisms involved in otitis media. We performed a systematic review of the literature reporting on the concordance between test results of nasopharyngeal and middle ear fluid samples for the most prevalent microorganisms in children with otitis media. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Van Dongen et al . [27], in a systematic review of the literature on the concordance between strains isolated from nasopharyngeal and MEF samples, found that H. influenzae strains were concordant in 80% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Van Dongen et al . [27], in a systematic review of the literature on the concordance between strains isolated from nasopharyngeal and MEF samples, found that H. influenzae strains were concordant in 80% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR and multiplex detection of five bacterial species have not been used for assessment of association between MEF and Nph microbiota in AOM patients before. Most studies evaluating concordance between MEF and Nph findings have used conventional culture, whereas PCR was employed in only 2 papers for analysis of a narrow set of species (Eser et al, 2009;Ueyama et al, 1995;van Dongen et al, 2013). Overall, results reported in the literature demonstrate modest to low PPVs (around 50%) for the most relevant microbes, but moderate to high NPVs, ranging from 68% to 97% (van Dongen et al, 2013).…”
Section: Pathogenmentioning
confidence: 99%
“…Most studies evaluating concordance between MEF and Nph findings have used conventional culture, whereas PCR was employed in only 2 papers for analysis of a narrow set of species (Eser et al, 2009;Ueyama et al, 1995;van Dongen et al, 2013). Overall, results reported in the literature demonstrate modest to low PPVs (around 50%) for the most relevant microbes, but moderate to high NPVs, ranging from 68% to 97% (van Dongen et al, 2013). In the present study, we observed higher PPVs for S. pneumoniae and H. influenzae than has previously been reported, which suggests better performance of the PCR method in predicting MEF findings.…”
Section: Pathogenmentioning
confidence: 99%
“…However, the negative predictive value of NP culture is usually high for SP or HI. 9 Consequently, because our study included only AOM patients with a single NP otopathogen, the AOM episode was unlikely due to a bacteria species other than the 1 recovered from the NP sample. Furthermore, the clinical characteristics of the 2 populations support the hypothesis that most AOM for which a single otopathogen is isolated from the NP are probably due to this species.…”
Section: Discussionmentioning
confidence: 99%
“…Concordance between results of these samples and MEF is globally moderate because 2 or even 3 otopathogens can be recovered from a sample, but typically only 1 is involved in AOM. 9 Therefore, the presence of a single otopathogen in the NP sample of children with AOM could more accurately reflect the bacteria involved in the AOM episode.…”
mentioning
confidence: 99%